Comparative evaluation of physical properties of commercially available silicone-based soft denture liners and acrylic-based soft denture liners - Rasleen Kaur Pahuja; Sameer Kaura; Neethu Roy (Wolters Kluwer Medknow Publications, 2020)
Elastic materials used in dental prosthetics to line removable dentures should be characterized by biocompatibility toward oral tissues, shape, and color stability; resistance to abrasion; and durability of the junction between the lining and the denture. The resilient lining materials present problems during clinical use, such as weakening of bond between lining and denture loss of resiliency, color alterations, and porosity. This review was aimed to compare and evaluate the physical properties of soft denture liners acrylic and silicone based and to determine which denture liners would be best suited for clinical usage. A review protocol was structured on the basis of the guidelines proposed by the PRISMA statement and Centre for Reviews and Dissemination. Overall, the results indicated that silicone-based soft denture liners performed significantly better than acrylic-based soft denture liners when compared for color stability, surface hardness, tensile bond strength, water sorption, and solubility, concluding that silicone-based soft liners would be better for long-term clinical use.